Minimum-component current-mode universal filter - Tangsrirat, Worapong; Channumsin, Orapin (My University, 2011)
This paper describes a current controllable current-mode universal filter with three inputs and one output using multi-output current-controlled current conveyors (MOCCCIIs). The proposed circuit consists of the minimum number of active and passive components, i.e. two MOCCCIIs and two grounded capacitors; simultaneous realization of all the standard filtering functions; independent current-control of the natural angular frequency (ω0) and bandwidth (BW); no requirement of component matching conditions; and low passive and active sensitivities. Copyright © 2011.
Keywords: Current-mode circuit; Second-generation current-controlled current conveyor; Universal filter